2023
DOI: 10.1371/journal.pone.0287610
|View full text |Cite
|
Sign up to set email alerts
|

How does the integration of cultural and tourism industries impact the value added to tourism value chain: Evidences from Jiangsu Province of China

Abstract: China has been fully implementing the policy of the cultural and tourism industrial integration since 2018. However, the value-added benefits of this policy are not prominent, and the relationship between industrial integration and the value added to the tourism value chain was seldom addressed by researchers. In the context of China’s high-quality development, it is necessary to conduct the impact of the integration of cultural and tourism industries on the value added to tourism value chain. This paper propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Second, the integration of the culture industry and tourism is predicated on technological amalgamation. The technological fusion within the culture and tourism industries enhances the resource development efficiency while simultaneously driving output towards high-value-added domains, such as creativity [56]. Meanwhile, the integration of the two major industries continuously facilitates the enhancement and optimization of products and services, thereby fostering economies of scale and ultimately bolstering the total productivity factor of the tourism industry.…”
Section: Theoretical Mechanism and Research Hypothesismentioning
confidence: 99%
“…Second, the integration of the culture industry and tourism is predicated on technological amalgamation. The technological fusion within the culture and tourism industries enhances the resource development efficiency while simultaneously driving output towards high-value-added domains, such as creativity [56]. Meanwhile, the integration of the two major industries continuously facilitates the enhancement and optimization of products and services, thereby fostering economies of scale and ultimately bolstering the total productivity factor of the tourism industry.…”
Section: Theoretical Mechanism and Research Hypothesismentioning
confidence: 99%
“…The commercialization process could introduce detrimental impacts on cultural aspects [ 46 ]. According to Zeng, Shen and Gu’s latest research findings [ 47 ], there is a single-threshold effect, indicating that a positive impact is only evident when the integration of culture and tourism reaches an elevated level. Currently, the conceptual scope and industrial boundaries of culture and tourism continue to expand, leading to new requirements for measuring and evaluating the integration level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, researchers have paid increasing attention to the empirical evaluation of policies on the integration of culture and tourism [ 8 ]. A study from China demonstrates that not all cities are suitable for implementing the policy of culture-tourism integration, as the policy performance may be poor in regions where the cultural industry is significantly less developed than the tourism industry [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, research into the impact of Swiss official development assistance on the number of visits and hotel accommodations from recipient countries found that international aid favorably boosts tourism numbers and expenditure in the aid-giving country [ 29 ]. Moreover, policies concerning climate [ 30 ], ecological preservation [ 31 ], economics[ 26 , 27 , 32 34 ], openness [ 35 , 36 ], public affairs [ 26 , 37 ], cultural-tourism integration [ 38 , 39 ], and high-speed rail commencement [ 40 , 41 ] have also been proven to influence tourism demand and economics. As the most rigorous and highest standard of selection policy in China, the study of the relationship and underlying mechanisms between the 5ATAs selection and tourism economics holds significant implications for the development of China’s tourism industry.…”
Section: Literature Reviewmentioning
confidence: 99%